A study on Article 121(1A) of federal constitution: issues on dispute over properties / Fara Nadia Hashim and Jay Ferrer Jeffrey Linjungan - Hashim, Fara Nadia; Jeffrey Linjungan, Jay Ferrer (2007)
When one of the parties in a non-Muslim marriage has converted to Islam, there will be conflicts as to which court they should go to to seek remedies. Article 121 (1A) makes the Civil Court not having jurisdiction over matters that already fall under the jurisdiction of the Syariah Courts. However, conflicts arise when it comes to implementation of Article 121 (1A). A non-Muslim does not have a locus standi in the Syariah Court hence they not allowed to bring their case to the Syariah Court. On the other hand, a Muslim could not bring his or her case to the Civil Court because a Muslim marriage falls within the jurisdiction of the Syariah Courts. These parties will have difficulties in searching for remedies that can help them to solve their disputes. Therefore, the purpose of this project is to examine the scope and limitation of Article 121(1 A) of the Federal Constitution, particularly on the issue on disputes over properties. In addition to that, the purpose of this project is to help the parties in seeking resolution to their problems. Our research has shown that problems still arise despite the introduction of Article 121 (1 A) into the Federal Constitution. When a party to a marriage becomes an apostate or converts to Islam and disputes over properties occur, conflict of laws soon follow. Our conclusion is that perhaps amendments need to be made to the relevant laws in order to reduce the conflicts between laws that are applicable in Malaysia.